Real-time multicomponent remote rehabilitation versus self-rehabilitation for sarcopenia: a randomized controlled trial protocol - Kexin Wang; Linbo Peng; Mingke You; Bin Shen; Jian Li (Journal of Orthopaedic Surgery and Research)
Abstract Introduction Sarcopenia is a progressive skeletal muscle disorder prevalent among older adults and is associated with increased risk of disability, falls, and mortality. Although resistance training and adequate nutritional intake are well-supported by clinical evidence, their implementation is often limited by poor adherence and insufficient access to supervised interventions. This trial aims to evaluate the effectiveness of a real-time multicomponent remote rehabilitation program versus standard self-rehabilitation in older adults with sarcopenia. Methods and analysis This single-center, randomized, controlled, two-arm trial will be conducted at West China Hospital, Sichuan University. A total of 104 community-dwelling adults aged 60–75 years meeting the Asian Working Group for Sarcopenia (AWGS) diagnostic criteria will be randomly assigned (1:1) to either an intervention or a control group. The intervention group will receive personalized exercise and dietary guidance via a WeChat-based application with daily remote supervision from therapists. The control group will receive non-interactive, text- and image-based static dietary guidance and unsupervised exercise instructions. The primary outcome is knee extensor strength at 12 weeks, assessed using a dynamometer. Secondary outcomes include knee flexor strength, handgrip strength, 6-metre gait speed, Timed Up and Go Test (TUGT), 6-minute walk distance (6MWT), and appendicular skeletal muscle mass index (ASMI), and reversal of sarcopenia. Outcomes will be assessed at baseline, week 6, and week 12 by blinded assessors. Statistical analysis will be performed using R software (v4.4.0), with P < 0.05 considered statistically significant. Ethics and dissemination This study was approved by the Ethics Committee of West China Hospital, Sichuan University, China (Approval No. 2024–2455). Results will be disseminated through peer-reviewed journals and academic conferences regardless of outcome direction. Trial registration number The trial is registered at ClinicalTrials.gov (registration number NCT06937073, April 2025).